Pengembangan Aplikasi Mobile "KantinKu" untuk Optimalisasi Layanan Kantin Universitas Bhayangkara Jakarta Raya - Dwipa Handayani; Andre Saputra Ginting (Jurnal Riset Informatika dan Teknologi Informasi, 2026)
The "KantinKu" application is a mobile digital solution designed to improve operational efficiency at Bhayangkara University Jakarta Raya's cafeteria. This research addresses manual system challenges such as long queues and recording errors through Project Charter development. Using needs analysis and iterative design methods, the application aims to provide quick food ordering solutions for customers and simplify real-time cafeteria transaction management. Development prospects include catering feature integration and expansion to other sectors, demonstrating the critical role of Project Charter in information technology project management.